Logística para mejorar la satisfacción laboral en el área de logística de EsSalud Iquitos 2025 - Bardales Tenazoa, Roy Smith (2025)
This study examined logistics and job satisfaction in the logistics department of ESSALUD Iquitos in 2025. It used a quantitative, descriptive-correlational, and non-experimental design to analyze the relationship between the two variables. A strong and significant positive correlation was found (Pearson r = 0.927, p = 0.000), showing that better logistics management is directly linked to higher job satisfaction levels. This supported the research hypothesis and rejected the null hypothesis. Additionally, the study highlights how logistics processes directly affect employee well-being, providing empirical evidence to guide health management decisions and recommending strengthening logistics strategies to improve the organizational climate.